2009
DOI: 10.1002/humu.20925
|View full text |Cite
|
Sign up to set email alerts
|

LGI1mutations in autosomal dominant and sporadic lateral temporal epilepsy

Abstract: Autosomal dominant lateral temporal epilepsy (ADLTE) or autosomal dominant partial epilepsy with auditory features (ADPEAF) is an inherited epileptic syndrome with onset in childhood/adolescence and benign evolution. The hallmark of the syndrome consists of typical auditory auras or ictal aphasia in most affected family members. ADTLE/ADPEAF is associated in about half of the families with mutations of the leucine-rich, glioma-inactivated 1 (LGI1) gene. In addition, de novo LGI1 mutations are found in about 2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
115
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(128 citation statements)
references
References 53 publications
8
115
0
4
Order By: Relevance
“…Also, uncertain is how LGI1 835delC functions in a dominant negative manner. Alternatively, another group suggests a loss of function mechanism based on the genetic facts that various types of mutations are associated with a rather homogenous phenotype (7). Phenotypes of LGI1 gene-targeted mice, increased seizure susceptibility in heterozygous LGI1 +/− mice and lethal epileptic seizures in homozygous LGI1 −/− mice provide supportive evidence for the haploinsufficiency mechanism of ADPEAF mutations in human; ADPEAF mutations perturb LGI1 secretion and reduce the LGI1-mediated transsynaptic connection between ADAM22 and ADAM23, leading to abnormal synaptic transmission and epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, uncertain is how LGI1 835delC functions in a dominant negative manner. Alternatively, another group suggests a loss of function mechanism based on the genetic facts that various types of mutations are associated with a rather homogenous phenotype (7). Phenotypes of LGI1 gene-targeted mice, increased seizure susceptibility in heterozygous LGI1 +/− mice and lethal epileptic seizures in homozygous LGI1 −/− mice provide supportive evidence for the haploinsufficiency mechanism of ADPEAF mutations in human; ADPEAF mutations perturb LGI1 secretion and reduce the LGI1-mediated transsynaptic connection between ADAM22 and ADAM23, leading to abnormal synaptic transmission and epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in LGI1 are linked to autosomal dominant partial epilepsy with auditory features (ADPEAF, also known as autosomal dominant lateral temporal lobe epilepsy [ADLTE]) (3)(4)(5), which is an inherited epileptic syndrome characterized by partial seizures with acoustic or visual hallucinations. So far, 25 LGI1 mutations have been described in familial ADPEAF patients and sporadic cases (7). Interestingly, at least six tested ADPEAF mutations all abolish LGI1 secretion (6,8).…”
mentioning
confidence: 99%
“…2,3 Its inheritance pattern is autosomal dominant with reduced penetrance (around 70%). Mutations associated with ADLTE are found in leucine-rich, glioma inactivated 1 (LGI1 [MIM: 604619]) [4][5][6] in 30%-50% of ADLTE-affected families. 3,7,8 Other genes harboring ADLTE-causing mutations are unknown.…”
mentioning
confidence: 99%
“…7,8,10 -15 Missense and truncation mutations have been found in both LRR and EPTP domains. Although previous studies have reported that pathogenic LGI1 mutations are uniformly distributed across the gene, 8 none has used a quantitative approach to assess mutation clustering or investigated genotype-phenotype correlations in detail. Establishment of genotype-phenotype associations has the potential to elucidate the biologic pathways involving LGI1, including the mechanisms leading to ADPEAF symptoms.…”
mentioning
confidence: 99%
“…8,9 To date, 33 unique LGI1 mutations have been reported in ADPEAF families (n ϭ 36) and sporadic patients with idiopathic focal epilepsy with auditory symptoms (n ϭ 2). 7,8,10 -15 Missense and truncation mutations have been found in both LRR and EPTP domains.…”
mentioning
confidence: 99%